Who is a theorist? - Eric Scerri (Universidad de Cádiz, 2011)
This article carefully analyzes a recent paper by Weisberg in which it is claimed that when Mendeleev discovered the periodic table he was not working as a modeler but instead as a theorist. I argue that Weisberg is mistaken in several respects and that the periodic table should be regarded as a classification, not as a theory. In the second part of the article an attempt is made to elevate the status of classifications by suggesting that they provide a form of 'side-ways explanation'.